Organizational buying - Marshall, Greg W. (Henry Stewart Talks, 2013)
The business marketplace, NAICS, Business versus consumer markets, Organizational buying situations, Typical buy class framework, Buying centers: participants and roles -Purchase decision making, Technology and organizational buying